ChemInform Abstract: Iron‐Catalyzed Asymmetric Hydrosilylation of Ketones. Issue 30 (July 2015) - Zuo, Ziqing; Zhang, Lei; Leng, Xuebing; Huang, Zheng
Abstract A new iron complex ligated by a chiral iminopyridine‐oxazoline is used as a highly efficient catalyst for asymmetric hydrosilylation reactions of aryl ketones to afford optically pure secondary aryl alcohols with moderate to high enantioselectivity.